Surveying Recent Literature on the Arabic and Persian Mirrors for Princes Genre - Marlow, Louise ca. 20./21. Jh. (History compass, 2009)
The study of the medieval Arabic and Persian ‘mirror for princes’ literatures in many respects resembles that of the similarly abundant literatures produced in Byzantium and the Latin West. In earlier scholarship, the predominant approach was that of the history of ideas, and scholars tended to focus on depictions of the ideal ruler and other aspects of the ‘political thought’ expressed in the mirror literatures. A secondary area of interest concerned textual transmission within and across these literatures. More recent scholarship has continued to develop and refine these established approaches, and has also developed new directions of research. Notably, several scholars have explored the Sitz im Leben of individual mirrors, and have studied their meaning and significance in the historical settings in and for which they were composed. Certain recent publications have highlighted the flexibility of mirrors, the multiple purposes they often served, the range of perspectives represented by their authors, and the importance of authors’ choices of language and genre in shaping the composition and reception of their works.